Natural Resource Conservation and Precision Farming : Proceedings of the National Seminar on Resources Conserving and Precision Farming/(Acc: (Acc: 3119) - Marathwada Agricultural University. Dept. of Agricultural Engineering (Lucknow : International Book Distributing Co., Pub. Division, 2005)
Contributed articles presented at the seminar with reference to India.
Keywords: Conservation of natural resources; Precision farming